Effects of Starter Cultures on the Metabolite Profile, Antioxidant Activities, and Anti-aging Properties of Tapuy Lees - Bragais, Edward Kevin B (Archīum Ateneo, 2025)
The Philippine rice wine (tapuy) and tapuy lees making process utilizes bubod, the traditional starter culture. The bubod contains variable number and species of microorganisms and influences the physical and chemical properties of tapuy and tapuy lees, resulting in inconsistent quality products. Hence, improvement and standardization of local starter culture are significant. Here, we examined the effects of well-defined starter cultures (Rhizopus oryzae (RO), Mucor indicus (MI), and Saccharomyces cerevisiae (SC)) and bubod on the metabolite profile, antioxidant, and anti-aging activities of tapuy lees. Our results showed the presence of polyphenols (102.36 ± 2.84 to 173.92 ± 3.88 μg GAE/g dry matter) in the tapuy lees, which are known for their bioactivities such as antioxidant, cellular protection, anti-inflammatory, and anti-aging. Additionally, the tapuy lees produced by RO + MI + SC starter exhibited the strongest scavenging activities against DPPH, hydroxyl, and superoxide radicals compared to bubod. The RO + MI + SC-produced tapuy lees extract significantly improved the lifespan, motility, and reproductive health of Caenorhabditis elegans, while boosting superoxide dismutase activity in vivo. These findings suggest that the use of well-defined starter cultures significantly enhances the health-promoting properties of tapuy lees. This research underscores the potential of tapuy lees as a functional food with antioxidant and anti-aging properties, suggesting its valuable role in promoting public health and preventing age-related diseases. Future studies should focus on clinical trials in humans to validate these findings and further explore the potential of tapuy lees as a natural, sustainable source of bioactive compounds.